Early Treatment Of Skeletal Class Iıı Anomalyıes (Case Report) - Seher Gündüz Arslan; Jalan Devecioğlu Kama (Galenos Yayinevi, 2004)
In this study, it was evaluated that the orthodontic and functional treatment of the two Class III cases characterized by maxillar skeletal retrusion, using protraction headgear and removable appliance. First case was a girl at 9.8 years old. She had skeletal Class III malocclusion. In intraoral examination it was observed that molar relationship was Class III and there was negative overjet (−1mm), in cephalometric analysis SNA, SNB and AMB angles were 74°, 77° and −3° respectively. The second case was also a girl 9.7 years old having Class III malocclusion. In intraoral examination of this case, Class III molar relationship and a negative overjet (−2 mm) in anterior region were observed. In cephalometric analysis, SNA, SNB and ANB angles were 74°, 78° and −4° respectively. In both cases, maxillar retrusion was treated by removable appliance and protraction headgear, the anchorage was supported by the first appliance. During the 8 months, the patients used the protraction headgear continuously. At the end of this period the patients had a good occlusion and maxillar retrusion was improved by early treatment.